Production of histamine and tyramine by bacteria isolated from Portuguese vacuum-packed cold-smoked fish - Silva, Manuela V. da (2011)
An agar medium containing histidine or tyrosine incubated anaerobically was used for detecting the decarboxylating activity of bacteria isolated from Portuguese vacuum-packed cold-smoked fish during chilled storage. The capacity of each bacterial isolate to produce histamine and tyramine was studied at 25 and 5 C incubated for 48 h and 10 days, respectively. More strains produced histamine and tyramine at 25 C compared with 5 C although lactic acid bacteria (LAB) strains exhibited similar results at the two different temperatures. Tyramine was produced by majority of the isolates tested although very low concentrations were produced at 5 C as confirmed by high-pressure liquid chromatography (HPLC). Tyrosine-agar was shown to be a good indicator medium for detection of bacteria that produced high levels of tyramine, since typical colonies surrounded by a translucent halo were easily recognised. LAB identified as Lc. Lactis lactis 1 and Carnobacterium divergens were detected as tyramine-producing bacteria. Acinetobacter spp. and Pseudomonas spp., isolated from all Portuguese smoked fish products, were negative on histidine-agar, but HPLC identified considerable quantities of histamine produced in a broth medium.